MICROENCAPSULATION OF CORIANDER OIL USING COMPLEX COACERVATION METHOD - CRISTIAN DIMA; ROMICA CRETU; PETRU ALEXE; ŞTEFAN DIMA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In the present study, the gelatin/gum Arabic/chitosan microcapsules encapsulating coriander oil were prepared by complex coacervation using glutaric aldehide and transglutaminase as hardening agents. The effects of wall materials, core/wall ratio, particle size, cross-linking agents, dispersing medium and temperature on the release of coacervate microcapsule were investigated. The antioxidative properties and antibacterial activity of free and microencapsulated coriander oil were examined. In the case of DPPH assay, the IC50 values of coriander oil free and coacervat microcapsule was comparables. Addition of chitosan in wall materials did not interfere with the antioxidant activity of coriander oil, but it improves the antibacterial activity of system. Coriander oil extraction by hydrodistillation revealed the influence of particle size on extraction yield. It increases with the decreasing of particle size resulting in maximum efficiency 0.836% for particles of 500 µm, 0.753% for those of 630 µm, and 0.704% for the size of 710 μm.